2007
DOI: 10.1119/1.2737473
|View full text |Cite
|
Sign up to set email alerts
|

An application of toroidal functions in electrostatics

Abstract: Quantitative analysis of the damping of magnet oscillations by eddy currents in aluminum foil Am. J. Phys. 80, 804 (2012) Rolling magnets down a conductive hill: Revisiting a classic demonstration of the effects of eddy currents Am. J. Phys. 80, 800 (2012) A semiquantitative treatment of surface charges in DC circuits Am. J. Phys. 80, 782 (2012) Relation between Poisson and Schrödinger equations Am. J. Phys. 80, 715 (2012) Magnetic dipole moment of a moving electric dipole Am.A method employing the use of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 14 publications
(10 reference statements)
0
18
0
Order By: Relevance
“…In connection to our interests here, the sketch of the electric field in the [xz] plane implicitly showed that the field, and thus the force on a point charge is not central. Selvaggi et al employed 22 a different approach and demonstrated -without detailed introduction of the toroidal functions-that the electric potential can be expressed in a compact form using the Fourier cosine expansion of the r − ξ −1 , in which expansion the toroidal functions appear as coefficients of the cos(mϕ) functions. This approach has some numerically attractive features: any non-uniform charge distribution can be systematically analyzed after calculating the Fourier expansion of the charge distribution on the ring, and for each term in this expansion there is a single corresponding toroidal function.…”
Section: General Formalism In a Nutshellmentioning
confidence: 99%
See 1 more Smart Citation
“…In connection to our interests here, the sketch of the electric field in the [xz] plane implicitly showed that the field, and thus the force on a point charge is not central. Selvaggi et al employed 22 a different approach and demonstrated -without detailed introduction of the toroidal functions-that the electric potential can be expressed in a compact form using the Fourier cosine expansion of the r − ξ −1 , in which expansion the toroidal functions appear as coefficients of the cos(mϕ) functions. This approach has some numerically attractive features: any non-uniform charge distribution can be systematically analyzed after calculating the Fourier expansion of the charge distribution on the ring, and for each term in this expansion there is a single corresponding toroidal function.…”
Section: General Formalism In a Nutshellmentioning
confidence: 99%
“…However, the choice of toroidal functions of first or second kind may require further thoughts. In Selvaggi et al 22 only the second kind is used, while in the mathematical literature it is used predominantly for the interior problem, r ⊥ < R.…”
Section: General Formalism In a Nutshellmentioning
confidence: 99%
“…It should be noted that restricted to (−1, 1), the functions P µ ν , 2Q µ ν are Hilbert transforms of each other (via 'Neumann's integral') when µ = 0, and are related by more complicated integral transforms when µ = 0 [35]. This relationship, which is suggested by (9), is why Q µ ν , Q µ ν and Q µ ν should really be defined to be twice as large. But to maintain compatibility with the past, the factor 1 2 implicit in their definitions will be kept.…”
Section: Normalizations and Asymptoticsmentioning
confidence: 99%
“…By (1b), it can be expressed in terms of the Legendre functions P ±m −s , and thus in terms of complete elliptic integrals. Legendre (rather than Ferrers) functions with ν a half-odd-integer and µ an integer are commonly called toroidal or 'anchor ring' functions, since harmonics including factors of the form P m n−1/2 (cosh ξ), Q m n−1/2 (cosh ξ) appear when solving boundary value problems in toroidal domains, upon separating variables in toroidal coordinates [9,10]. The efficient calculation of values of toroidal functions, employing recurrences or other numerical schemes, is well understood [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The right hand side of Eq. 8is the zeroth order toroidal harmonic expansion for the inverse distance function in circular cylindrical coordinates [21][22][23][24][25][26][27] and can be derived directly from the free-space Green's function in circular cylindrical coordinates [28][29][30]. Figures 2 and 3 are plots which illustrate a comparison between Eqs.…”
Section: The Yukawa-potential Kernel Of a Circular Cylindrical Sourcementioning
confidence: 99%